Protection against frosts by antifreeze, amino acids, and vermicompost in phenological stages of the bean - Calderón-Tomás, Celene; Díaz-Ruiz, Ramón; Contreras-Ramos, Juan; Pérez-Ramírez, Efraín (Revista Mexicana de Ciencias Agrícolas, 2023)
Bean cultivation is one of the main activities of the peasant economy in Mexico; however, it is subjected to different types of stress, where frosts significantly affect its cultivation, for this reason, it is necessary to look for alternatives that provide greater tolerance to plants. Thus, the objective was to evaluate the effect of different products against frosts on the stem, in the vegetative (V) phenological stages of the bean. The research was conducted in the greenhouse of the Puebla Campus of the College of Postgraduates in 2018. The Negrito CP variety was used, which was sown in expanded polystyrene cups. The treatments used were antifreeze (10 ml L-1 of water), amino acids (1.5 g L-1 of water), and the mixture of both in the same dose used individually; these were applied with an interval of 48 h and 96 h and exposed to a simulated frost in a freezer of magnitude equal to 0 °C for 1.5 h. The frosts presented different effects on the vegetative stages of the bean, the most tolerant were V1 and V2. The leaves were the most damaged, followed by the petioles and stem. The treatments that provided the greatest protection to the bean seedlings were An (antifreeze) and the combination Ver+An (vermicompost+antifreeze).
Keywords: Phaseolus vulgaris L.; phenology; stress